A chorus of color: hierarchical and graded information content of rapid color change signals in chameleons. (12th June 2018) - Ligon, Russell A; McGraw, Kevin J
Abstract : Dynamic color signals represent a rare signaling strategy but there are numerous parallels between rapid color changes and the vocalizations used to mediate aggressive interactions in other taxa. Here, we used a robochameleon to elicit color change from live chameleons and linked these signals to individual-specific performance and behavior. Abstract: Animals rely on information-rich signals to minimize costs associated with competition. If fighting ability is linked to stable individual attributes (e.g., morphology), the signals that communicate information about such ability should be relatively static. Conversely, the temporal variability of motivation should favor dynamic threat signals that indicate an animal's current likelihood of escalating a contest. Though static color ornaments are used by many animals to signal quality or fighting ability, the function of dynamic color change as a social signal has only recently begun to be investigated. Here, we examined the information content of rapid physiological color changes displayed by adult male veiled chameleons Chamaeleo calyptratus during agonistic interactions by conducting experimental trials between live chameleons and standardized, experimentally controlled robochameleon models. Chameleons reliably communicated motivation with dynamic color displays—individuals that brightened were 14 times more likely to approach the robochameleon than nonbrightening individuals. Additionally, chameleons with shorter latencies to maximum stripe brightness had stronger bites, and those displaying brighter, yellower stripes exhibited more aggression. The parallels between dynamic color changes and the vocalizations used to mediate aggressive interactions in other taxa are numerous. The use of particular vocalizations/color changes can signal motivation levels while specific signal elements (e.g., pitch, timing, brightness) may be linked to fighting ability. Because the complexity and potential information content of color signals increases markedly when organisms can display context-specific variation in the expression of these ornaments, the study of dynamic color signals is a field ripe for the investigation of complex visual and signaling strategies.